Growth, yield and biochemical responses of BARI chhola-9 (Cicer arietinum L.) to GA3 and rhizobium application - Jahan, Tasnia; Khan, Farhana Islam; Adam, AMM Golam; Begum, Hasna Hena (Bangladesh Journal of Botany, 2018)
A field experiment was conducted to investigate the responses of various concentrations of GA3 (10, 20, 50 ppm) and Rhizobium inoculation on growth, yield and biochemical parameters of BARI Chhola-9. Foliar application of 50 ppm GA3 resulted maximum plant height, number of primary branches per plant, shoot and root length, fresh and dry weight of shoot and root and biomass duration per plant with significant variations in case of fresh and dry weight of shoot and biomass duration. The stimulatory effect of 50 ppm GA3 on number of pods per plant, fresh and dry weight of pods per plant, number of seeds per pod, number of seeds and straw yield per plant and weight of 1000-seed eventually produced 4.76% higher yield over the control. Yield parameters of BARI Chhola-9 showed almost negative response to Rhizobium and 10 ppm treatments with a few exceptions. Pigment content of leaves also increased due to 50 ppm GA3 treatment at both vegetative and flowering stages where, significantly higher amount of chlorophyll a and b were recorded from flowering stage although statistically similar to 20 ppm GA3 treatment. However, protein content of leaves increased following Rhizobium and 10 ppm GA3 treatments at vegetative stage and to all treatments at flowering stage but, increase in protein content of seeds was recorded from Rhizobium treatment only. Out of four treatments, 50 ppm produced better yield.